Human Rights in Islam: A Model for Universal Dignity and Prosperity - Arif, Dr. Shoaib (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
Islamic teachings provide a broad base for human rights, emphasizing dignity, justice, equality, and social responsibility. The Qur’an and Sunnah outline rights dealing with life, property, education, gender parity, and freedom of belief that ensure all human beings receive respect and are treated fairly. These principles aim at protecting against oppression, guaranteeing welfare, and ensuring governance with ethics. Islamic human rights are universal, with an emphasis on both individual and collective well-being. Concepts such as Adl (justice), Ihsan (excellence), Tazkiyah (self-purification), and Shura (consultation) underpin the guiding philosophy for moral conduct and interaction in society and governance. By integrating the spiritual, ethical, and social imperatives, Islam presents human rights as a set of practical responsibilities that protect dignity and ensure prosperity, rather than ideals. This article explores the basic tenets of human rights in Islam, their practice throughout history, and their relevance as a model for universal human dignity and socioeconomic flourishing in societies today.